Perkembangan Tradisi Senandung di Kabupaten Asahan - Soiman Soiman; Khairul Arif; Nurhayati Marpaung (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2021)
Culture is a habit that is present in society and has benefits for maintaining and developing a way of life. There are so many traditional cultures that exist in Asahan Regency, researchers decided to choose the "Senandung Tradition" which comes from Malay culture in Asahan Regency, North Sumatra. This study intends to obtain a description of how the development of the humming tradition in Asahan Regency. The type of research writing this time is the type of anthropological writing with ethnographic studies, in which the researcher focuses on discussing the culture that exists in the community so that this study uses a qualitative method with the approach used, namely a descriptive approach. The results of this study indicate that the development of the Sounding Tradition has decreased every year. Although there are still people who are still actively using the Sounding Tradition to fill the events that are held, there are also some people who are starting to leave this tradition.